Exploring The Financial Dynamics Of Green Building Adoption: Insights From Indonesia - Sutikno Sutikno; Sarwono Hardjomuljadi; Hendrik Sulistio; M. Agung Wibowo; Suyono Dikun (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This research purpose is to offer insights to property owners and developers whose focus tends to be solely on the initial costs of green buildings, and aligning with the requirements set forth by Minister of Public Works and Public Housing Regulation No. 21 of 2022, effective from 2022, which mandates green buildings to obtain Building Structure Approval (PBG) and Functional Worthiness Certificate (SLF). Drawing from the 2013-2018 Green Building Council Indonesia (GBCI) report, which indicates a mere 2% certification rate for buildings exceeding 12 floors, this study seizes the opportunity to delve into how green building considerations influence financial decisions. Surveying 102 experienced respondents in green building practices, this research employs green building factor analysis, value engineering, life cycle cost analysis, and Structural Equation Modeling (SEM)-PLS to scrutinize the factors influencing cost performance in green buildings. The findings spotlight 10 critical green building factors pivotal for securing certification, alongside unveiling correlations between initial costs, operational costs, and life cycle costs. Anticipated outcomes encompass facilitating compliance with Minister of Public Works and Public Housing Regulation No. 21 of 2021, and nurturing the development of green buildings in Indonesia. Implications span regulatory compliance, informed financial strategies, green building advancement, and knowledge dissemination. This study aims to simplify comprehension of the financial ramifications of green buildings, furnishing practical guidance for developers in navigating the intricacies of cost-sustainability equilibrium.